As vozes sussurrantes do inconsciente em Acenos e afagos de João Gilberto Noll - Moreira, Marcel (2024)
Literature presents itself as a privileged space where the voices of the collective and the trans-experiential character of the human being can manifest themselves. In Acenos e afagos (2008) by João Gilberto Noll, the protagonist goes through a process of gender transformation that extends to the body in and through language. This transformation is constructed through literary strategies that can be observed in the unfolding of the novel's narrative voice. This research seeks to reflect on the origin of these multiple voices and what literary effects it produces within the novel, on the reader's reception and, more broadly, on the society for which it is intended. Thus, the answer that the research proposes is constructed from two points of view: I- literary criticism; II- analytical psychology. With regard to literary criticism, the multiplication of voices is part of a process of pronominal obliqueness, as Alexandre Nodari (2019) theorizes, gaining complexity within the narrative with the aim of exposing the modern subject (the reader) to the mirror that reflects its own condition of multiplicity and, thus, creating the possibility of perceptions and experiments that transcend its ambient world or its apparent reality, in a process of trans-umweltization, which is described by Gabriel Catren (2022). While, from the point of view of analytical psychology theory, the multiplicity of voices and the symbolism of gender variation portrayed in the novel are marks of the manifestation of the collective unconscious in the literary work. The symbolic and distorted image of the archetype of Anima and Animus, represented in the novel, is a form of collective questioning of a social structure